Machine Learning for Early Detection of Alzheimer’s Disease from Brain MRI - Cherian, Iype; Agnihotri, Aditya; Katkoori, Arun Kumar; Prasad , Versha (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Recent years have seen an uptick in the use of computed tomography (CT) and magnetic resonance imaging (MRI) scans to create three-dimensional images of the human body for use in medical image processing studies. Immunisations and medical treatment do not work to prevent or treat chronic diseases. Some examples of chronic ailments are asthma, cancer, heart disease, diabetes, and Alzheimer’s disease. Alzheimer’s disease is a progressive neurodegenerative illness that destroys both memory and personality over time. Without regular checks, diseases like Alzheimer’s could not be seen until they’ve progressed to a fatal level. Millions of individuals throughout the globe are living with Alzheimer’s disease, which is a leading cause of death. The first indicator of Alzheimer’s disease may be moderate cognitive and/or behavioural impairment, followed by preclinical illness and, ultimately, full-blown Alzheimer’s disease. This machine learning model outperforms state-of-the-art medical ailment prediction methods. Most machine learning algorithms for Alzheimer’s disease identification are limited to low-dimensional feature spaces because of the sparsity problem. Research in this article examines the feasibility of using several methods such as deep learning, machine learning, and transfer learning approaches to create an early Alzheimer’s disease diagnosis.